Drug consumption and treatment costs of the glaucoma therapy in the Republic of Serbia - Ćoškov Aleksandra D.; Savanović Dijana R.; Todorović Nemanja B.; Lalić-Popović Mladena N.; Tomić Nataša Z.; Milijašević Boris Ž. (Hospital Pharmacology)
Introduction: Glaucoma is the leading cause of the irreversible blindness, affecting more than 70 million people worldwide. Drug therapy is the primary treatment for glaucoma due to its effectiveness, safety, practicality, and cost-effectiveness. Aim: The aim of this study is the analysis of the consumption and costs of the medication therapy for glaucoma on a monthly and annual basis per patient in the Republic of Serbia in the period from 2015 to 2020. Material and Methods: This study employs a retrospective analysis of data collected from the official websites of the Agency for Medicines and Medical Devices of Serbia and the Institute of Public Health of Serbia "Dr Milan Jovanovic Batut" for the period from 2015 to 2020. to examine the consumption and costs of antiglaucoma medicines in the Republic of Serbia. Results: The data on the consumption of the local antiglaucoma therapy, as well as the price of monthly and annual therapy per patient in the period from 2015 to 2020 is shown. Drugs that are consumed the most were prostaglandin analogues (latanoprost) and beta-blockers (timolol). The most frequently prescribed among the fixed combinations were timolol-dorzolamide and timolol-latanoprost. The number of glaucoma patients fluctuated over a five-year period in the Republic of Serbia. Conclusion: Based on the research, latanoprost is the most commonly used medicine in antiglaucoma therapy, followed by timolol and fixed combination of timolol-dorzolamide. Between 2015 and 2020, prices for all medications generally decreased and the most affordable choice was timolol.